Viabilidade de grãos de pólen de espécies de Paspalum após a criopreservação visando seu uso em programas de melhoramento genético - Dinato, Naiana Barbosa (Universidade Federal de São Carlos, 2020)
Paspalum is a genus of the Poaceae family, native to America, of which many species have forage potential. The high natural genetic diversity observed in the genus can be used to obtain and launch new cultivars. For hybridization to occur, one of the premises is that the flowering period between parents is synchronized. Collecting pollen from the male parent and storing it until the female parent is ready is an alternative to asynchronous flowering. This study aimed to determine the pollen morphology and viability of pollen grains from Paspalum atratum, P. malacophyllum and P. regnellii cryopreserved for 12 months and their use in intra and interspecific crosses, thus confirming their viability in vivo. Pollen grains were collected in pots in a greenhouse, at Embrapa Pecuária Sudeste, with three replicates of each treatment. Two dehydrating agents (LiCl and silica gel) were tested for three different times (30 ', 60' and 120 ') and a treatment without dehydration. After slow thawing, pollen grains were evaluated for viability by staining with 0.25% tetrazolium solution. Freshly harvested grains were also evaluated as controls. It was observed that the pollen grains remained viable after 12 months when they were dehydrated with lithium chloride for 30 minutes and silica gel for 120 minutes, being that they were statistically equal to the control. Such treatments can be considered as good protocols for long-term conservation of Paspalum pollen. The cryopreserved pollen grains were also tested for viability in vivo, being observed under fluorescence microscopy. The following intra and interspecific crosses were performed between January and February 2018: P. urvillei (BGP 393) x P. malacophyllum (BGP 6; BGP 293); P. urvillei x P. regnellii (BGP 215, plant F1 # 37 (P. plicatulum 4PT x P. guenoarum cv. Azulão) x P. atratum (BGP 98; BGP 308). The spikelets were removed periodically, for different times after pollination, fixed in FAA solution (1: formaldehyde, 1: glacial acetic acid, 8: 80% ethyl alcohol) for 30 minutes and stored in 70% ethanol. It was observed that in all crosses there was effective germination of grains of pollen tube and that in some crossings the pollen tube reached the micropyle. For pollen morphological characterization, lactic acetolysis and SEM photomicrography (scanning electron microscopy) were performed. The result of the morphometric analyzes showed that the pollen grains had a spheroidal prolate shape and subprolate, that there is no ornamentation in the exine and that there is little difference in size between the species evaluated. As proof of the viability and efficacy of cryopreserved pollen grains, these were used in intra and interspecific crosses in order to elucidate the capacity of the grain to produce viable seeds and to enable hybridization between Paspalum species using cryopreserved pollen grains. The pollen grains were stored in liquid nitrogen for about 12 months, when crosses between different species were made in the combinations: (1) P. urvillei (BGP 393) x P. malacophyllum (BGP 6; BGP 293); (2) P. urvillei (BGP 393) x P. regnellii (BGP 215); (3) 366_C 33 (P. regnellii / BGP 258 x P. regnellii / BGP 397) x P. malacophyllum (BGP 293), (4) 365_C 33 (P. regnellii / BGP 258 x P. regnellii / BGP 397) x P. regnellii (BGP 215); (5) P. regnellii (BGP 258) x P. regnellii (BGP 215); (6) F1 # 10, F1 # 4, F1 # 37 and F1 # 42 plants (P. plicatulum 4PT x P. guenoarum cv. Azulão) x P. atratum (BGP 98; BGP 308) and (7) F1 # 10 and F1 # 37 plants (P. plicatulum 4PT x P. guenoarum cv. Azulão) x P. malacophyllum (BGP 293). 5850 spikelets were pollinated in all combinations, resulting in 830 caryopses, of which 445 seedlings germinated. The morphological characterization of the progenies was carried out based on Paspalum morphological descriptors. Male and female parents shared similar characteristics and in some crosses, it was not possible to differentiate hybrids by morphology. In no intersection was it possible to perform multivariate analysis based on main components. Therefore, to confirm the hybrid character of the individuals, an analysis was performed using microsatellite (SSR) and inter-microsatellite (ISSR) markers. Molecular markers were selected in the literature based on the species for which they were developed and / or evaluated. It was observed that, of the seven ISSR markers tested, five managed to differentiate the parents of some crosses: (CT) 8-G, (AC) 8-T, (CA)8-G, (ATG) 5-GA and (GA) 8-C), and of the 50 SSR selected, 16 differentiated the parents from the crosses performed. At least four polymorphic markers were evaluated for each crossing. A total of 73 hybrids were identified, including all crosses performed. In view of the results, it is possible to conclude that pollen grains from Paspalum have high viability after cryopreservation for up to 365 days, if dehydrated with lithium chloride and / or silica gel. Fluorescence microscopy showed that cryopreserved pollen grains germinated effectively in stigma and in some cases, the micropyle was affected. In intra and interspecific crosses using these pollen grains, it was possible to identify hybrids using molecular markers, so cryopreserved pollen grains can be used in breeding programs to enable synchrony between asynchronous flowering species.
Viability of pollen grains from Paspalum species after cryopreservation for use in breeding programs
Keywords: Paspalum atratum; Paspalum malacophyllum; Paspalum regnellii; Paspalum urvillei; Criopreservação; Viabilidade de grãos de pólen; Cryopreservation; Pollen grains viability; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA VEGETAL